Rhetoric in the Service of Roman Comedy. Some Remerks on Jokes and Puns - Skwara, Ewa (My University, 2023)
Roman comedy eagerly uses various types of rhetorical figures mainly to construct comic scenes and puns. Alliteration, anaphora, epiphora are all part of the comedic tool-box, homonym and paronomasia, however, allow Plautus and Terence not only to arouse cheerfulness in their viewers, but also to balance on the edge of good taste. If similarly sounding words produce dirty connotations, it is surely the viewers mind, that is responsible for the association. This article presents examples of various types of rhetorical figures used in comedic situations, with particular emphasis on such a variant in which no one comments on the joke on the stage, so it is difficult to state clearly whether this iocus dubius was intended by the playwright or is the result of the audience’s frivolous connotations. It seems that such “unconfirmed” jokes usually refer to obscene subjects, but Plautus and Terence use them in different ways.
Keywords: Terence; Plautus; Comedy; Palliate; epiphora; equivocation; ambiguity; double entendre; alliteration; anaphora; homonym; paronomasia